A newborn patient with both annular pancreas and Meckel's diverticulum: A case report of an unusual association. Issue 17 (April 2018) - Cai, Peng; Zhu, Zhenwei; Chen, Jianlei; Chen, Lulu; Pan, Jiang; Zhi, Wenxian; Zhu, Jie; Wu, Bin; Gu, Zhicheng; Huang, Shungen; Wang, Jian
Abstract: Rationale: Annular pancreas (AP) is recognized as a cause of duodenal obstruction in children, while children with Meckel's diverticulum (MD) are usually asymptomatic. Here we present a rare case with both AP and MD, which was identified by abdominal exploration during diamond-shaped duodenoduodenostomy. Patient concerns: A "double-bubble" sign was found by ultrasound at 35 week of pregnancy. After 39 weeks of pregnancy, the male patient was transferred to the Department of General Surgery, Children's Hospital of Soochow University because of a suspected duodenal stenosis. Diagnoses: Preoperative abdominal X-ray examination indicated "double-bubble" sign. AP was confirmed by exploratory surgery, with an MD located 30 cm above the ileocecal valve. Interventions: Diamond-shaped duodenoduodenostomy and a wedge resection of the intestine with end-to-end anastomosis were performed Outcomes: The patient recovered and his appetite was good without vomiting. Lessons: Our experience demonstrates that abdominal exploration is essential for children with gastrointestinal malformations.